2022
DOI: 10.3389/fphys.2022.984429
|View full text |Cite
|
Sign up to set email alerts
|

Abscopal effects of thoracic X-ray radiation on spermatogenesis in mice

Abstract: The study aimed to elucidate abscopal effects of thoracic X-ray irradiation on spermatogenesis in mice. Male C57BL/6 mice were randomly divided into sham group and radiation group, and subjected to thorax fractionated X-ray irradiation or sham irradiation with the total dose of 5 Gy/day for each animal for four consecutive days. After irradiation, sperm morphology was observed, and sperm number was counted under microscope, and sperm apoptosis was detected by flow cytometry. Meanwhile, testis index was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover, previous studies have demonstrated that CRS can induce severe oxidative stress, leading to diminished antioxidase activity and increased ROS levels [ 49 ]. Elevated MDA contents have been detected in the sperm of individuals with conditions such as oligozoospermia or asthenozoospermia [ 50 ], indicating a strong association between sperm damage and excessive oxidative stress [ 8 ]. Notably, oxidative stress has been closely linked to depression as well [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have demonstrated that CRS can induce severe oxidative stress, leading to diminished antioxidase activity and increased ROS levels [ 49 ]. Elevated MDA contents have been detected in the sperm of individuals with conditions such as oligozoospermia or asthenozoospermia [ 50 ], indicating a strong association between sperm damage and excessive oxidative stress [ 8 ]. Notably, oxidative stress has been closely linked to depression as well [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the realm of clinical practice, various diagnostic tests are employed to determine the presence of MI and ascertain its underlying causes. For example, sperm quality can be evaluated by assessing motility and morphology rates [ 8 ]. Analyzing physiological markers such as prolactin (PRL), gonadotropin releasing hormone (GnRH), follicle stimulating hormone (FSH), and testosterone (T) can offer insights into gonadal function [ 9 ].…”
Section: Introductionmentioning
confidence: 99%